Mechanical Performance of Untreated and Treated Sugarcane Bagasse Reinforced Epoxy Composite - NURUL ALIA BINTI ABDUL HAMID; Mohamad, Zaleha (Research Progress in Mechanical and Manufacturing Engineering, 2026)
This research explores about mechanical performance of sugarcane bagasse (SCB) fiber-reinforced with epoxy composite by examining the effect of alkali treatment. A sustainable way to reinforce polymer matrices is by using agricultural waste, such as SCB. The study classifies both the condition untreated and NaOH-treated SCB fibers in three different compositions, such as 5%, 4%, and 3%. Composite samples were produced and subjected to tensile and flexural tests. This testing refers to ASTM D3039 for tensile, while ASTM D790 for flexural. The results indicate that SCB treated with alkali enhanced fiber-matrix adhesion, which then improved mechanical performance. The composite with 5% treated SCB had the best tensile and flexural strength, thanks to better fiber spread and strong bonding at the interface. This study shows that using agricultural waste like SCB can improve composite performance and promote sustainability.